Shank3 related muscular hypotonia is accompanied by increased intracellular calcium concentrations and ion channel dysregulation in striated muscle tissue - Yildiz, Berra; Schiedt, Lisa; Mulaw, Medhanie; Bockmann, Jürgen; Jesse, Sarah; Lutz, Anne-Kathrin; Boeckers, Tobias M. (Frontiers in Cell and Developmental Biology, 2023)
Phelan-McDermid syndrome (PMS) is a syndromic form of Autism Spectrum Disorders (ASD) classified as a rare genetic neurodevelopmental disorder featuring global developmental delay, absent or delayed speech, ASD-like behaviour and neonatal skeletal muscle hypotonia. PMS is caused by a heterozygous deletion of the distal end of chromosome 22q13.3 or SHANK3 mutations. We analyzed striated muscles of newborn Shank3Δ11(-/-) animals and found a significant enlargement of the sarcoplasmic reticulum as previously seen in adult Shank3Δ11(-/-) mice, indicative of a Shank3-dependent and not compensatory mechanism for this structural alteration. We analyzed transcriptional differences by RNA-sequencing of muscle tissue of neonatal Shank3Δ11(-/-) mice and compared those to Shank3(+/+) controls. We found significant differences in gene expression of ion channels crucial for muscle contraction and for molecules involved in calcium ion regulation. In addition, calcium storage- (i.e. Calsequestrin (CSQ)), calcium secretion- and calcium- related signaling- proteins were found to be affected. By immunostainings and Western blot analyses we could confirm these findings both in Shank3Δ11(-/-) mice and PMS patient muscle tissue. Moreover, alterations could be induced in vitro by the selective downregulation of Shank3 in C2C12 myotubes. Our results emphasize that SHANK3 levels directly or indirectly regulate calcium homeostasis in a cell autonomous manner that might contribute to muscular hypotonia especially seen in the newborn.